2016
DOI: 10.3389/fmicb.2016.01195
|View full text |Cite
|
Sign up to set email alerts
|

An Alkaline Protease from Bacillus pumilus MP 27: Functional Analysis of Its Binding Model toward Its Applications As Detergent Additive

Abstract: A proteolytic strain of Bacillus pumilus MP 27 was isolated from water samples of Southern ocean produced alkaline protease. Since protease production need expensive ingredients, an economically viable process was developed by using low cost carbon source, wheat straw, supplemented with peptone. This protease was active within temperature ranges 10–70°C at pH 9. This process was optimized by response surface methodology using a Box Bekhman design by Design Expert 7.0 software that increased the protease activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 52 publications
0
39
1
Order By: Relevance
“…Another study reported similar optimum pH for protease production (36). Furthermore, there were also reports that the best pH for protease production was 8.0(37), 9.0 (38), 10.0 (39), and 11.0 (38,40). The pH value affects the absorption of nutrients by affecting the degree of ionization of the nutrients, cell membrane charge and membrane permeability.…”
Section: Optimization Of Culture Conditions For Proteasementioning
confidence: 87%
“…Another study reported similar optimum pH for protease production (36). Furthermore, there were also reports that the best pH for protease production was 8.0(37), 9.0 (38), 10.0 (39), and 11.0 (38,40). The pH value affects the absorption of nutrients by affecting the degree of ionization of the nutrients, cell membrane charge and membrane permeability.…”
Section: Optimization Of Culture Conditions For Proteasementioning
confidence: 87%
“…Hence, this alkaline protease can be used as an additive in commercial detergent, as it is also effective in removing stains in cold water washes. 48 Alkaline serine protease was isolated from Bacillus licheniformis NH1. The protease was active from pH 7-12 with an optimum pH of 10-11.…”
Section: Detergentsmentioning
confidence: 99%
“…All of these are well suited to detergent formulations particularly at alkaline pH (Sumantha et al 2006). Protease from Bacillus pumilus MP 27 was considered as a good candidate for detergent industry due to its broad substrate range, activity over high and low temperatures and pH, and compatibility with surfactants and commercial detergents (Baweja et al 2016). Bacillus subtilis KT004404, an isolate from hydrothermal vents, produced a metalloprotease that has high resistance towards anionic surfactants, solvents and detergents.…”
Section: Proteases In Detergent Industrymentioning
confidence: 99%
“…There are several reports of thermostable and wide range pH stable proteases from Bacillus spp. which have excellent compatibility for industrial processes (Baweja et al 2016;Guleria et al 2016). The genus Bacillus is represented by Gram-positive, spore-forming, rod-shape bacteria that are obligate aerobes or facultative anaerobes (Dijl and Hecker 2013).…”
Section: Introductionmentioning
confidence: 99%